User Experience Optimization: A Usability Testing Approach to Application Development - Nugraha, Ucu; Amalia, Endang; Harahap, Parlindungan (SEAN Institute, 2024)
A comprehensive approach to optimizing User Experience (UX) through the application of Usability Testing methods in application development. The research background discusses the importance of UX in the context of modern applications and how usability testing is the key to improving the quality of user experience. An in-depth literature review was conducted to understand the concept of usability testing and identify relevant current methods. The research methodology includes a research design that combines usability testing case studies on two different applications. The testing process involves collecting data from active users using various evaluation methods, such as observation, interviews, and performance measurement. Evaluation results are analyzed to identify aspects that require improvement, with a focus on improving key aspects of UX.